A Crosstalk Between Brain Cholesterol Oxidation and Glucose Metabolism in Alzheimer’s Disease - Gamba, Paola; Staurenghi, Erica; Testa, Gabriella; Giannelli, Serena; Sottero, Barbara; Leonarduzzi, Gabriella (Frontiers in Neuroscience, 2019)
In Alzheimer’s disease (AD), both cholesterol and glucose dysmetabolism precede the onset of memory deficit and contribute to the disease’s progression. It is indeed now believed that oxidized cholesterol in the form of oxysterols and altered glucose uptake are the main triggers in AD affecting production and clearance of Aβ, and tau phosphorylation. However, only a few studies highlight the relationship between them, suggesting the importance of further extensive studies on this topic. Recently, a molecular link was demonstrated between cholesterol oxidative metabolism and glucose uptake in the brain. In particular, 27-hydroxycholesterol, a key linker between hypercholesterolemia and the increased AD risk, is considered a biomarker for reduced glucose metabolism. In fact, its excess increases the activity of the renin-angiotensin system in the brain, thus reducing insulin-mediated glucose uptake, which has a major impact on brain functioning. Despite this important evidence regarding the role of 27-hydroxycholesterol in regulating glucose uptake by neurons, the involvement of other cholesterol oxidation products that have been clearly demonstrated to be key players in AD cannot be ruled out. This review highlights the current understanding of the potential role of cholesterol and glucose dysmetabolism in AD progression, and the bidirectional crosstalk between these two phenomena.